Analysis and calibration of a water distribution systems 9 a case study of Port Dickson (volume I/II) / Kamal Bahrin Jaafar - Jaafar, Kamal Bahrin (1993)
Water distribution system is a common topic among engineers and would-be engineers. Such topics about water distribution system always recur from time to time. This is partly due to the inefficient system of the existing water distribution systems. As such, a new research needs to be carried out. The main reason of this research is to identify an effective method of examining the problems that occur in a chosen system. In this project, the method used is the combination of the computer simulation and field measurement, based on base demand, demand weighting and demand pattern at nodes of the chosen system. During this project, two major problems have been encountered. One of the problems is leakage. While the other problem is the influence of coefficent of pipe (C) in the chosen pipe. Leakage, being one of the major problems of this project is measured by measuring the minimum night flow, legitimate night flow and T-factor. As for the second problem, mis project shows how the C value should be determined by using Wal&ld Technique. However, the ratio value of the headloss between the predicted and actual, should be more than one.